Social Construction Of Halalan Thayyiban And Halal Food Law Among Faith-Based Communities, Banten Indonesia - Ikomatussuniah, Ikomatussuniah (2022)
This study focuses on the social constructs of halalan thayyiban and halal food laws among the faith-based communities in the province of Banten, Indonesia. Halal food has been widely understood by the general public to be food that does not contain pork, khamr (alcohol or other form of intoxicants) and animal protein slaughtered using the Islamic method. While halalan thayyiban is an inseparable concept, not many understand about it. In fact, research and theories of halalan thayyiban food law are very limited, if not non-existent. Hence, this study aims to fill in the theoretical and empirical gaps of halalan thayyiban food law in the literature. The province of Banten in Indonesia is chosen as the study area because it is regarded as the largest halal valley industry in Indonesia.